Interaction of zinc and vitamin A in rats receiving a regional diet of Manaus, Amazonas, Brazil. Effect of supplementation with vitamin A, zinc and zinc and vitamin A - Yuyama, Lucia Kiyoko Ozaki; Cozzolino, Sílvia Maria Franciscato (Archivos Latinoamericanos de Nutricion, 1996)
The interaction of zinc and vitamin A in rats receiving a regional diet of Manaus, supplemented with vitamin A, zinc and zinc and vitamina A was studied. The regional diet was elaborated according to data of Shrimpton and Giugliano (6), for families receiving less than two minimun salaries. The biological test to study the interaction was based on the depletion of zinc and vitamin A in rats in the period of lactation, and a period of repletion where supplements of zinc (0.82 mg %) and vitamin A (94,2 μ.g %) were given, either separately or together, according to the recommendations of the Committee on Laboratory Animal Diets (7). From the results, it was concluded that there was an interaction of these nutrients in terms of mobilization of hepatic vittamin A. Although the regional diet of Manaus did not meet the zinc RDA, the amount present was enough to utilize the available vitamin A. Although the amount of zinc present in the diet, as determined by parameters of biovailability, such as growth, concentration in organs and zinc-dependent enzymes, was adequately used by the animals, probably due to promoting factors in the diet. The Manaus regional diet needs to be supplemented with vitamin A in order to maintain the hepatic reserves, and with zinc, to maintain the normal levels of vitamin A in plasma.
Keywords: Retinol; Zinc; Animals; Brasil; Diet Supplementation; Female; Male; Rat; Wistar Rat; Animal; Brasil; Female; Food, Fortified; Male; Rats; Rats, Wistar; Vitamin A; Zinc